The functional or program-based budgets and their application in Peru - Althaus, Miguel de (1968)
The present article analyzes the importance of functional or program budgets in the public sector, as well as their implementation in Peru. In this context, the author defines functional budgets as a tool for public planning and management that allows for the allocation of public resources based on specific objectives, through the identification of programs and projects that can best contribute to achieving said objectives. On the other hand, it is established that the implementation of such program budgets in Peru has posed a series of challenges and difficulties due to the lack of serious plans, the broad powers of the legislative branch, as well as the null capacity for monitoring and the lack of continuous evaluation of programs by the government. Therefore, the question arises as to whether the program budget system really fits the reality of the country, or if it is rather a utopian system.